THE EFFICACY OF MELDONIUM IN REDUCTION OF CARDIAC ELECTRICAL INSTABILITY IN PATIENTS WITH ISCHEMIC STROKE - A. A. Abdullaev; A. D. Magomedov; U. A. Islamova; Z. R. Umahanova (Столичная издательская компания, 2015)
Aim. To study meldonium effect in the combination therapy for ventricular repolarization disorders and cardiac electrical instability in patients with ischemic stroke. Material and methods. Patients (n=46) with acute phase of ischemic stroke were included in a randomized, open-label, uncontrolled study. Patients were randomized into two groups. Group 1 patients (n=25) had been receiving meldonium (Mildronate;Grindex,Latvia;Pharmstandard,Russia), 1.0 g/day intravenously once daily, as a part of standard therapy for 10 days since admission to the hospital. Group 2 patients (n=21) had standard therapy alone. A standart 12-lead ECG, ventricular late potentials (VLP), 24-hour Holter monitoring, troponin test were performed at the baseline and after 10 days. Results. Patients of the group 1 as compared to the group 2 demonstrated more significant positive effect on the clinical condition of patients with ischemic stroke, ventricular repolarization, reduction of frequency (from 3.7±0.5 to 2.1±0.4; p<0.05) and duration (from 6.6±1, 3 to 4.0±1.1 min; p<0.05) of painless myocardial ischemia episodes and VLP (from 48 to 32%). Conclusion. Adding meldonium to standard therapy in patients with acute phase of ischemic stroke can have a positive effect on the clinical condition, repolarization disorders on ECG, frequency of VLP and episodes of painless myocardial ischemia detection. This may have a positive effect on the electrical stability and prevention of cardiac arrhythmias.